Conditioned turning and functional recovery after unilateral substantia nigra lesion in rats. - Mattioli, R.; Bueno, J. L.; Tomaz, C. (My University, 1988)
In order to investigate whether conditioned circling interferes with recovery from turning induced by unilateral substantia nigra (SN) lesion, rats were trained to turn either ipsi- or contralateral to the lesioned side before and after the lesion was made. Two yoked groups served as controls. The number of turns contralateral to the trained side was significantly lower in relation to the pre-lesion value for the ipsilateral trained group and remained so until the end of the experiment. A partial recovery was observed on the 19th post-lesion day for the contralateral trained group. The results are discussed in terms of additive effects from training and the lesion symptoms.